2008
DOI: 10.1623/hysj.53.5.1013
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of channel degradation rates in urbanizing watersheds

Abstract: In urbanizing watersheds, as land use changes, and storm sewers and impervious surfaces are increased, both the frequency and magnitude of discharge increase, resulting in stream channel down-cutting and widening and related loss of structures and engineering works. A simple model for assessing the time rate of degradation in watersheds is given. The model relies on a continuous simulation of watershed discharge based on local climate (SWAT-DEG) instead of a dominant discharge approach. Unique to this approach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 36 publications
0
13
0
Order By: Relevance
“…For instance, the authors noted an abrupt increase in the flow rate when the forest cover was low (range of 17 to 37%) and, conversely, the lowest flows occurred when the forest cover was greatest (range of 59 to 81%). Finally, other researchers have demonstrated the propagation difference of a flood wave during rainfall before and after urbanization of an area (Camorani et al 2005, Allen et al 2008. With regard to the study area, the urbanized areas remain marginal such that they do not truly constitute a limiting factor in the exacerbation of surface runoff.…”
Section: Land-use Changes and Flood-risk Areasmentioning
confidence: 91%
See 1 more Smart Citation
“…For instance, the authors noted an abrupt increase in the flow rate when the forest cover was low (range of 17 to 37%) and, conversely, the lowest flows occurred when the forest cover was greatest (range of 59 to 81%). Finally, other researchers have demonstrated the propagation difference of a flood wave during rainfall before and after urbanization of an area (Camorani et al 2005, Allen et al 2008. With regard to the study area, the urbanized areas remain marginal such that they do not truly constitute a limiting factor in the exacerbation of surface runoff.…”
Section: Land-use Changes and Flood-risk Areasmentioning
confidence: 91%
“…Lastly, the small proportion of forest land in this area, as well as in the upstream part of the catchment (Castonguay et Saint-Laurent 2009, suggests that it cannot be a determining factor in the overall assessment of the intercepted waters during periods of heavy rain. It is known that the type and density of the vegetation cover, as well as urbanization, have a direct impact on surface runoff and, as a result, on the hydrological response of rivers and streams (Chase et al 2000, Reynard et al 2001, Rey et al 2004, Wissmar and Timm 2004, Camorani et al 2005, Ferreira et al 2005, Allen et al 2008, Toba and Ohta 2008, Huaxia et al 2009). The vegetation cover not only allows rainwater to be intercepted, but its efficacy is dependent on the proportion of its coverage, distribution and type (e.g.…”
Section: Land-use Changes and Flood-risk Areasmentioning
confidence: 99%
“…Within the model cascade, SWAT is used to simulate runoff contribution and sediment input from the catchment to the reach. Although SWAT's channel erodibility processes have shown to give comparable degradation results to a HEC-RAS model (Allen et al, 2008), SWAT's spatial representation through subbasins is disadvantageous for obtaining differentiated instream results along a stream channel since the same result value is given for each reach, which can be many kilometres long. The decision to use a separate instream model for depicting processes in the main channel is thus driven by the need for high resolution results with output parameters that the SWAT model is not able to supply, e.g.…”
Section: Description Of the Model Cascadementioning
confidence: 99%
“…The contribution by Allen et al (2008) deals with prediction of channel degradation rates in urbanizing watersheds, where both the frequency and magnitude of discharge increase due to the increase in storm sewers and impervious surfaces. This leads to stream channel downcutting and widening, and the related loss of engineering works and structures.…”
Section: This Special Issue On Advances In Ecohydrological Modellingmentioning
confidence: 99%
“…Horn et al (2004) and Migliaccio et al (2006) concluded that further testing and refinement of the SWAT in-stream algorithms is required. Improved stream channel degradation and sediment deposition routines are necessary to better describe sediment transport, improving on the simple channel and degradation routines described by Allen et al (2008). Channel sediment routing could be improved by accounting for sediment size effects, with separate algorithms for wash load and bed load.…”
Section: Directions For Future Researchmentioning
confidence: 99%